Religião e capital social na periferia urbana do Grande abc paulista uma análise das redes sociais pentecostais no município - Noronha, Claudio Pereira (2010)
This research analyzes pentecostal evangelical churches in city of Rio Grande da Serra, in Great ABC region from São Paulo state. Search to identify which is the social paper of these religious groups of great growth in the city among its members in fragile social economic situation, as much how much for the poor of the city. From a reflection concerning the constitution of "peripheral" territorial spaces, and associative practices in these spaces, our objective is to study the formal and informal religious associations, and the construction of social networks around them, and their contribution for the increase of the social expansion, understood this, according to Bourdieu, as aggregate of material and symbolic benefits of their participants. The research leads in consideration the city is characterized for the being a periphery region, where important parcel of the population lives in situation of segregation, risks and social vulnerability.(AU)